السياحة البيئية كآلية لتحقيق التنمية المستدامة - قدوري ،فؤاد العربي; بوكي، تونفيق (جامعة الوادي University of Eloued, 2025)
تساهم البيئة بكل مكوناتها الطبيعية والبشرية في تقدم وازدهار النشاط السياحي، كما يمكن أن تكون السياحة عاملا أساسيا في حماية البيئة عندما تتكيف مع البيئة المحلية عن طريق وضع آليات إدارية سليمة تضمن جلب عدد كبير من السياح لهاته المواقع مما ينعكس إيجابيا على التنمية الاقتصادية بشرط المحافظة على المكونات الإيكولوجية للبيئة باعتبارها تعد رأس المال الحقيقي للسياحة. . يهدف هذا المقال إلى إبراز دور السياحة البيئية في التنمية الاقتصادية دون المساس بحقوق الأجيال القادمة في سد حاجياتهم السياحية وتحقيق طموحاتهم في هذا المجال ويمكن الاستنتاج من هذا المقال إنه حتى نضمن سياحة بيئية قائمة على اعتبارات بيئية يجب توفر عدة شروط منها: ترقية وتحسين الخدمة العمومية العناية بالبيئة بكل مكوناتها رفع الوعي البيئي لدى أفراد المجتمع. دمج التربية البيئية ضمن المناهج التعليمية. The environment, with all its natural and human components, contributes to the progress and prosperity of touristic activity, and tourism can also be a major factor In protecting the environment, when it is adapted to the local environment, by setting up sound management mechanisms that ensure bringing in a large number of tourists These sites have a positive impact on economic development and on the condition that the ecological components of the environment are preserved The real capital of tourism. This article aims to highlight the role of ecotourism in economic development without prejudice to the rights of future generations to satisfy Their touristic needs and achieve their ambitions in this area. It can be concluded from this article that in order to guarantee eco-tourism based on environmental considerations, several conditions must be taken into consideration like: Promotion and improvement of public service; Taking care of the environment with all its components; Raising environmental awareness among community members; Integration of environmental education into educational curricula. Enter your abstract here (an abstract is a brief, comprehensive summary of the contents of the article .
Ecotourism as a mechanism for achieving sustainable development
Keywords: السياحة; البيئة; التنمية المستدامة; tourism; environment; sustainable development.